2017
DOI: 10.1016/j.tecto.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Gaps, tears and seismic anisotropy around the subducting slabs of the Antilles

Abstract: Seismic anisotropy in and beneath the subducting slabs of the Antilles is investigated using observations of shear-wave splitting. We use a combination of teleseismic and local events recorded at three-component broadband seismic stations on every major island in the area to map anisotropy in the crust, the mantle wedge and the slab/sub-slab mantle. To date this is the most comprehensive study of anisotropy in this region, involving 52 stations from 8 seismic networks. Local event delay times (0.21±0.12s) do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 80 publications
2
32
1
Order By: Relevance
“…Benford et al (2012) proposed a simple model in which mantle anisotropy was dominated by large‐scale lithospheric fabrics associated with the large transform fault zones that bisect the north and south of the island. However, further to the east other studies prefer subslab trench‐parallel mantle flow with an isotropic mantle above (Lynner & Long, 2013; Meighan & Pulliam, 2013;Piñero‐Feliciangeli & Kendall, 2008; Schlaphorst et al, 2017). Both these mechanisms would generate seismic anisotropy with an east to west trending fast polarization direction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benford et al (2012) proposed a simple model in which mantle anisotropy was dominated by large‐scale lithospheric fabrics associated with the large transform fault zones that bisect the north and south of the island. However, further to the east other studies prefer subslab trench‐parallel mantle flow with an isotropic mantle above (Lynner & Long, 2013; Meighan & Pulliam, 2013;Piñero‐Feliciangeli & Kendall, 2008; Schlaphorst et al, 2017). Both these mechanisms would generate seismic anisotropy with an east to west trending fast polarization direction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to the east, in the region of Puerto Rico, suggest the mantle wedge above the slab does not provide a significant anisotropic contribution compared to the subslab mantle (Piñero‐Feliciangeli & Kendall, 2008; Schlaphorst et al, 2017). Schlaphorst et al (2017) observed a mean dt measurment of 0.21 s from seismicity associated with the slab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial variability in seismicity along the arc has also been attributed to the effects of the subducting fracture zones [20]. The dramatic variations in crustal properties might suggest complicated upper mantle wedge dynamics, which would explain why the seismic properties of the upper mantle wedge beneath the LAA appear to be isotropic [62,63].…”
Section: Discussionmentioning
confidence: 99%